HIGH-PERFORMANCE THIN-LAYER CHROMATOGRAPHY ANALYSIS AND FREE RADICAL SCAVENGING POTENTIAL OF SOUTH INDIAN ORTHODOX BLACK TEA - Rajamani, Mahalakshmi; Krishnasamy, Kalaivani; Abubakker, Nishadh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to evaluate the free radical scavenging potential and high-performance thin-layer chromatography (HPTLC) fingerprinting of the ethanolic extract of south Indian orthodox black tea (OBT). Methods: Phytochemical analysis was carried out using standard methods, and free radical scavenging activity of the extract was determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH), nitric oxide (NO), superoxide anion (SOD), and hydroxyl radical scavenging capacities. The ethanolic extract of OBT was loaded in the pre-coated HPTLC plates (silica gel 60 F 254) E-MERCK KGaA. HPTLC was carried out with toluene: ethyl acetate: diethylamine (7:2:1), chloroform: methanol:formic acid (8.5:1.0:0.5), and butanol: isopropyl alcohol (1:1) as mobile phase for alkaloids, flavonoids, and terpenoids, respectively. Results: HPTLC results confirmed that the extract contained several potential active components such as flavonoids, alkaloids, and terpenoids as the slides revealed multicolored bands of varying intensities. Extract of OBT reliably showed the total phenolics 132.27 mg/g, flavonoids 72.52 mg/g, and alkaloids 66.01 mg/g of dry matter. The IC50 value of OBT for DPPH was found to be 372.22 Î¼g/ml, SOD 311.93 Î¼g/ml, NO 362.17 Î¼g/ml, hydroxyl radical 342.14 Î¼g/ml, and reducing power 178.54 Î¼g/ml. Conclusion: The HPTLC fingerprinting profile developed for ethanolic extract will help in proper identification and quantification of marker compounds. The ethanolic extract of OBT was found to possess a wide range of phytochemicals with excellent antioxidant properties. This information may help to choose the best beverage to be consumed in the future.